Agrárörökségünk: az alföldi parasztgazdálkodás a 18–19. században (kiállításismertető) - Surányi, Béla (Gerundium, 2013)
OUR AGRICULTURAL HERITAGE: PEASANT ECONOMY IN THE 18TH AND 19TH CENTURIES. In joint co-operation between the Agricultural and Economic Centre of the University of Debrecen and the Board of Directors of the Museums of Hajdú–Bihar County (Déri Museum), in April, 2013, a permanent exhibition was opened at the Agrarian Centre with the title ”Peasant Economy of the Plains Region in the 18th and 19th Centuries”. The permanent display of the museum presents the traditions of the plains-region economy from the end of the 18th century to the beginning of the 20th century in the most characteristic areas of a primarily market-town economy: agriculture, animal husbandry, and viniculture. he text printed here treats original objects, archival photographs and graphic material made at the beginning of the 20th century.